THE IMPLEMENTATION OF PEER EDITING TECHNIQUE TO IMPROVE STUDENTS’ WRITING ACHIEVEMENT - Hanafziah Miftahul Fajri; Rita Inderawati; Soni Mirizon (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: This study aimed to find out whether or not there was a significant difference in recount writing achievement of the tenth grade students of SMA Negeri 3 Prabumulih between those who were taught through Peer editing Technique and those who were not and to find out whether or not there was a significant difference in recount writing achievement after the students were taught through Peer editing Technique. The sample was 58 students which were taken by using purposive sampling method. A quasi-experimental study was used. The calculation was done by using SPSS (Statistical Package for Social Science) version 21. The result of paired sample t-test in experimental group showed the t-obtained was higher than the critical value of t-table (9.087 > 2.041). It could be stated that there was a significant difference in the recount writing achievement before and after the treatment in the experimental group. In addition, the independent sample t-test showed the t-obtained was also higher than t-table after students‟ mean score was calculated (8.474 > 2.003). It can be concluded that there was a significant difference in recount writing achievement between the students who were taught through Peer editing Technique (experimental group) and those who were not (control group). In brief, Peer editing Technique was effective in improving students‟ recount writing achievement.Key words: Peer editing Technique, Recount Writing Achievement, tenth graders